1999
DOI: 10.1507/endocrj.46.179
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Amyloid Goiter Secondary to Crohn's Disease.

Abstract: Abstract.We herewith report a case of amyloid goiter secondary to Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Amyloidosis is characterized by the deposition of fibrillary proteins that can accumulate in various organs [ 49 ] and is classified as primary or secondary. Secondary amyloidosis is a well-known complication of CD, as demonstrated by previous studies, and has an incidence of 0.5%–9.0% [ 42 , 48 ]. However, the prevalence of amyloidosis is less in UC patients.…”
Section: Ag In Ibdmentioning
confidence: 99%
“…Amyloidosis is characterized by the deposition of fibrillary proteins that can accumulate in various organs [ 49 ] and is classified as primary or secondary. Secondary amyloidosis is a well-known complication of CD, as demonstrated by previous studies, and has an incidence of 0.5%–9.0% [ 42 , 48 ]. However, the prevalence of amyloidosis is less in UC patients.…”
Section: Ag In Ibdmentioning
confidence: 99%
“…In primary amyloidosis, amount of monoclonal plasma cells increase in bone marrow, similarly immunoglobulin light chains (AL type) increase in the affected tissue. Secondary amyloidosis accompanies malignancies or chronic inflammatory diseases such as tuberculosis, rheumatoid arthritis, ankylosing spondylitis, cystic fibrosis, bronchiectasis and inflammatory bowl disease 6 . Approximately, 75% of patients with secondary amyloidosis that accompanying to CD are male, just as our case 14–16 .…”
Section: Discussionmentioning
confidence: 59%
“…The association of CD with amyloidosis is a rare entity that first time reported by Moschkowitz in 1936 14,15,21 . Afterwards, Olson et al reported a case of secondary amyloidosis related to CD, in 1948 6 . Since then, some similar cases and reviews reported by various authors, between 1982 and 2009 22,23 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Deposition of amyloid in the thyroid gland may occur in a number of different disease conditions. It occurs in about 50% to 70% of medullary thyroid carcinoma, secondary to long standing inflammatory conditions such as rheumatoid arthritis [2], cystic fibrosis [3] [4], ankylosing sponilitis [5] and Crohn's disease [6]. AG may also be secondary to long standing chronic infectious inflammatory diseases such as bronchiectasis [7] and tuberculosis [8].…”
Section: Introductionmentioning
confidence: 99%